2021
DOI: 10.1111/rode.12835
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and vulnerability in Mozambique: An analysis of dynamics and correlates in light of the Covid‐19 crisis using synthetic panels

Abstract: This study aims at providing new insights into poverty, vulnerability, and their correlates in Mozambique, applying synthetic panels techniques and expanding on earlier analyses. Our results suggest that there is a high degree of poverty immobility, especially in rural areas in the northern and central regions and for low‐educated people. Even nonpoor households are at a high risk to vulnerability, and this risk does not differ much for households in urban/rural areas or in different regions or with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Indeed, even small shocks in generally poorer rural areas can push many households below the poverty line, whereas urban households hit by comparatively larger shocks could still end up with consumption levels above the poverty line. The higher probability of falling into poverty for households in rural areas is in line with Salvucci and Tarp ( 2021 ). In their study, they also found that the probability of becoming poor had decreased over time from 2008/2009 to 2014/2015.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Indeed, even small shocks in generally poorer rural areas can push many households below the poverty line, whereas urban households hit by comparatively larger shocks could still end up with consumption levels above the poverty line. The higher probability of falling into poverty for households in rural areas is in line with Salvucci and Tarp ( 2021 ). In their study, they also found that the probability of becoming poor had decreased over time from 2008/2009 to 2014/2015.…”
Section: Resultssupporting
confidence: 78%
“…Yet, we also found that the longer-term structural drivers of poverty are still at work during the COVID-19 shock: people in rural areas, working in agriculture and/or as family workers without remuneration, or working in services associated with the family, not or less educated, are among the worst-hit population groups in terms of likelihood of falling into poverty. Surely, additional drivers of vulnerability emerged due to COVID-19, which are not simply additional to standard drivers, as also highlighted in Salvucci and Tarp (2021).…”
Section: Policy Recommendations and Conclusionmentioning
confidence: 97%
“…Zambézia province is in north-central Mozambique. Zambézia is home to 5.1 million people (2017) and is one of the poorest regions in the world [ 54 ]. About half (51%) of adults over 15 are literate [ 55 , 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to Fobra and Mavundla [80] and Nuvunga et al [81], some phenomena, such as the devaluation of metical (the local currency), an increase in interest rate, and inflation, have added to high-profile financial scandals and crises and discouraged investors. The International Monetary Fund (IMF) was among such investors [82].…”
Section: Political Economymentioning
confidence: 99%
“…Mozambique is a low-income country [95], among the world's poorest economies [82], with an average gross domestic product (GDP) per capita of USD 493 [96] in 2020 and USD 503 in 2021 [95], with 60% resulting from the informal sector [83]. The GDP is significantly (40%) generated in informal activities [93] and the sector is expanding [83].…”
Section: Economic Growth and Developmentmentioning
confidence: 99%